Critical thinking and problem solving skills among engineering students at public universities in Malaysia - Ismail, W.; Ali Saifuddin, W.O.; Noraini, H. (2018)
Engineering Education is a course that emphasized on soft skills that is related to critical thinking and the ability in solving certain problems. Creative and Critical Thinking Skills (CCTS) or in Malay it is called Kemahiran Berfikir secara Kreatif dan Kritis (KBKK) is a type of skill that is deeply emphasis in the education system. It starts from primary school. Recently, all the exam questions in primary schools, secondary schools and public universities are oriented to the principle Higher Order Thinking Skills (HOTS) in (RMK 11 - Transforming Education System). The objective of the program is to produce students that are more competent in solving problems by using various forms of knowledge that had been studied theoretically in order to applying it effectively. This study aims to examine the extent to which the needs of elements of critical thinking and problem solving skills to produce Competitive Engineers from industries view. The quantitative method used to distribute the questionnaire. A total of 300 respondents were participated in this study. The study is expected to be a guide for future engineers who would be involve accordance with the requirements of the mainstream industry.